Globus y Gea. Sobre el sentido de la guerra en el pensamiento de Franz Rosenzweig y Jan Patǒcka - Garrido Maturano, Ángel Enrique (2025)
The article confronts the interpretation of the meaning of the First World War in the thought of F. Rosenzweig and J. Patočka. The confrontation is developed on the basis of the hermeneutic scheme of war as a means of configuration of the world as Globus and war as a means of annihilation of the world as Gea. The analysis of the differences between the two thinkers regarding the foundations and aims of war and its relation to peace leads to two conclusions. First, that the meaning each philosopher attributes to war presupposes an essentially different understanding of the world as such. Secondly, that, despite their divergences, both converge in the view that war can only be overcome by a revelation of a divine character involving sacrifice.